Beda Czcigodny i bohaterowie "Historii kościelnej narodu angielskiego" w "Żywotach świętych" Piotra Skargi - Bernadetta Puchalska-Dąbrowska (Vox Patrum, 2016)
The aim of the article is the analysis of the heroes, themes and motives of Bede’s Ecclesiastical History of the English People present in Lives of Saints by Piotr Skarga. The Polish author of the 16th-17th centuries refers to selected characters, stories and themes as sources of role models and for polemical purposes. Bede’s heroes: bishops, missionaries, the religious, secular rulers, serve as examples for the implementation of the specific virtues. Selected motives of the chronicle treated by Skarga – in most cases – with fidelity to the original, are intended to show not only the distant reality unknown to the Polish reader, but also the characters and events meaningful in the post-Trent period.